The gut microbiota and gut disease. Issue 10 (18th October 2021) - Fehily, Sasha R.; Basnayake, Chamara; Wright, Emily K.; Kamm, Michael A.
Abstract: The gut microbiota has a key role in the maintenance of good health, and in the pathogenesis of gastrointestinal diseases. These conditions include the inflammatory bowel diseases, colorectal cancer, coeliac disease and metabolic liver disease. Although the nature of the microbial disturbance in these conditions has not been fully characterised, this has not prevented the development of microbially based therapies. Microbial‐changing therapies may address newly recognised pathophysiological contributors of disease and have the potential to replace or supplement standard therapies. Antibiotics play a role in initial Clostridiodes difficile disease and some specific inflammatory disorders. Probiotics have a more limited proven role. Faecal microbiota transplantation is of proven therapeutic benefit in recurrent C. difficile disease and ulcerative colitis. We review the current literature for microbiota‐targeted therapies in gut disorders.